Gestão de crises de âmbito policial - Rodrigues, Manuel Maria Ferreira Carneiro (2013)
The issues concerning Crisis Situations under the scope of police activity, raised after incidents considered critical, has emerged with greater intensity during the most recent decades, posing a major challenge for police forces around the world. These are situations or events of crucial importance, involving hostage taken or barricaded individuals, in which inevitably human lives are at risk, requiring from law enforcement agencies a specific response capability, i.e., a type of intervention not framed under the parameters considered as routine, in order to obtain solutions to minimize the possibility of casualties. Because this is about impacting situations of extreme gravity, where the preservation of human lives is concerned and, in many cases, the very Rule of Law as well, we understand the need for police forces to adapt to new procedures and working methods. Such procedures are an enormously complex task that requires the coordination and articulation of several components, including not infrequently the performance of different police forces, as well as organizations and entities with varied powers and duties, which implies the need for effective management. This explains the emergence of Crisis Management Structures, imposing to determine which are their fundamental components, their importance, how they interconnect, and their major goal. The intrinsic features will also be analyzed in the aspect that we consider to be the fundamental groundwork of a Crisis Management Structure, i.e., Negotiation itself, considering it as a kind of police intervention, where a wide range of procedures feeds a channel of dialogue, aiming at minimizing the damage resultant from an extreme action, in particular, to prevent the death of any of those involved. This is in essence the path we have chosen to develop this study, trying to find out an answer to the fundamental question: What model of Crisis Management Structure should be adopted to manage a critical event involving hostage negotiation?